Real-world outcomes of maintenance therapy post-autologous stem cell transplantation in newly diagnosed multiple myeloma - Ka-Won Kang; Dae Sik Kim; Se Ryeon Lee; Mi Hwa Heo; Hyeon-Seok Eom; Jongheon Jung; Ji Hyun Lee; Sung-Hyun Kim; Youngil Koh; Chang-Ki Min; Seung Shin Lee; Sung-Nam Lim; et al. (BMC Cancer)
Abstract Background In the Republic of Korea, only lenalidomide, bortezomib, ixazomib, and thalidomide monotherapy are available as maintenance therapy post-autologous stem cell transplantation (ASCT). Methods To determine whether maintenance therapy confers a survival benefit in the real world, we compared treatment outcomes according to the use and type of maintenance therapy in patients who underwent ASCT following frontline therapy with the triplet regimen of bortezomib, thalidomide, and dexamethasone for newly diagnosed multiple myeloma in 15 nationwide centers. Results A total of 512 patients were analyzed (no-maintenance group, n = 359, and maintenance group, n = 153 patients). Among those receiving maintenance therapy, 104 (68%) received thalidomide, 33 (21%) lenalidomide, and 16 (10%) bortezomib or ixazomib. The median progression-free survival (PFS) from the time of ASCT was 26.4 and 44.1 months in the no-maintenance and maintenance groups, respectively. In the multivariate analysis, the use of maintenance therapy was significantly associated with better PFS. After adjustment for the type and duration of maintenance therapy, the use of bortezomib or ixazomib was associated with better PFS than other drugs. Longer duration of therapy was associated with improved PFS. No statistically significant difference was observed in overall survival and secondary malignancy rates by use or type of maintenance. Conclusion Despite practical limitations, maintenance therapy after ASCT demonstrated a gain in PFS in the real world, and there was no clear increase in the risk of secondary malignancy. Therefore, it may be prudent to consider implementing maintenance therapy in a feasible manner.